Globalization 2017
DOI: 10.1007/978-3-662-49502-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Good Times and Bad Times, with Endogenous Trade Policy Responses

Abstract: Globalisation is associated with long periods of sustained economic growth and credit expansion, whereas major recessions tend to lead to falling trade and protectionism. I investigate this, using a model where an important component of trade is search by rms trying out new trade partners. To model this, I set up a schematic model of upstream-downstream matching between rms, where match quality determines prots. Prior to globalisation, Northern upstream and downstream rms work together, to avoid trade costs. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Alternatively, Sedlacek & Sterk (2017) link expansion of the intensive margin of sales to cumulative marketing expenditure: it is highly likely that this is something which can be postponed, if the firm is faced with an uncertain future barrier. Secondly, while simpler models of firm exit might predict that exit will only happen when a negative trade event actually occurs (rather than in advance), this is not the case where trading involves renewing contracts or renewing search (Edwards 2017), in which case withdrawal of firms may well be spread out over the period before the final policy decision, as firms come to the point where they need to renew ties. Finally, if firms' search process consists of a series of trial and error contracts, then those who have not yet found good matches would be expected to withdraw pending a negative anticipated shock.…”
Section: The Nature Of the Shockmentioning
confidence: 99%
“…Alternatively, Sedlacek & Sterk (2017) link expansion of the intensive margin of sales to cumulative marketing expenditure: it is highly likely that this is something which can be postponed, if the firm is faced with an uncertain future barrier. Secondly, while simpler models of firm exit might predict that exit will only happen when a negative trade event actually occurs (rather than in advance), this is not the case where trading involves renewing contracts or renewing search (Edwards 2017), in which case withdrawal of firms may well be spread out over the period before the final policy decision, as firms come to the point where they need to renew ties. Finally, if firms' search process consists of a series of trial and error contracts, then those who have not yet found good matches would be expected to withdraw pending a negative anticipated shock.…”
Section: The Nature Of the Shockmentioning
confidence: 99%